Animal personality and state–behaviour feedbacks: a review and guide for empiricists. (January 2015) - Sih, Andrew; Mathot, Kimberley J.; Moirón, María; Montiglio, Pierre-Olivier; Wolf, Max; Dingemanse, Niels J.
Highlights: Animal personalities can be explained by state–behaviour positive feedback loops. Relevant state variables include both intrinsic and extrinsic factors. We discuss experimental and statistical methods for studying state–behaviour feedbacks. Abstract : An exciting area in behavioural ecology focuses on understanding why animals exhibit consistent among-individual differences in behaviour (animal personalities). Animal personality has been proposed to emerge as an adaptation to individual differences in state variables, leading to the question of why individuals differ consistently in state. Recent theory emphasizes the role that positive feedbacks between state and behaviour can play in producing consistent among-individual covariance between state and behaviour, hence state-dependent personality. We review the role of feedbacks in recent models of adaptive personalities, and provide guidelines for empirical testing of model assumptions and predictions. We discuss the importance of the mediating effects of ecology on these feedbacks, and provide a roadmap for including state–behaviour feedbacks in behavioural ecology research.